Zora Neale Hurston entre espaços de experiência e horizontes de expectativas: ou a trajetória de uma escritora e intelectual negra do/no século XX - Melo, Carolina Nascimento de (2025)
This dissertation explores the multifaceted trajectory of Zora Neale Hurston, an American Black writer, anthropologist, and intellectual active between the 19th and 20th centuries. The study examines the intricate articulations among culture, race, and gender within a historical context where race largely dictated public, academic, and cultural discourse in the United States. The research posits that culture, more than race, should be understood as the central stage for symbolic disputes and the possibilities for creative agency among Black populations. Its impacts are observable both in their daily lives and in the historical changes they spearheaded. To achieve this, utilizing the concepts of articulation, space of experience, and horizon of expectations, the work investigates how Hurston, through her writing and academic-cultural engagement, managed to challenge hegemonic paradigms and inaugurate literary and political genealogies that resonate with contemporary and global Black intellectual thought. The methodological foundation of the research is structured around three main approaches: the use of (con)textual interludes as a narrative and analytical strategy; the application of the circuit of culture as a lens for observing the contingencies of circumstances that allowed her a distinct role in her socio-historical context; and the African diaspora as a theoretical and political key for understanding practices of being and existing in the world that differed from those delimited by colonialist systems. Hurston's collection at the University of Florida served as a primary source, enabling the retrieval of memories, documents, and productions that, while narrating a life, also highlight the paths and the creation of other ways of existing and signifying the world.